FRACTAL MODEL OF THE UNIVERSE - Maksyuta, N. V. (Одеські астрономічні публікації, 2017)
In the paper for the first time from the point of view of knots theory it is considered a fractal model of the Universe. In the frames of this model it is shown that to explain its regular evolution it is necessary to adopt a conception that a physical vacuum is crystal-like. As a result it is proposed new approaches to the nature of "dark matter" and a relic radiation